Improving Medical Student Mentorship in Orthopaedic Surgery - Tarrant, Seth; Behzadpour, Vafa; McCormack, Thomas; Cline, Justin; Willis, Jordan; Mendez, Gregory; Zackula, Rosalee; Dart, Bradley; Hearon, Bernard (Kansas Journal of Medicine, 2023)
Introduction. Owing to limited clinical clerkships and travel restrictions related to COVID-19, recent medical student mentorship in orthopaedic surgery has been negatively impacted. The purpose of this Quality Improvement (QI) project was to determine if medical student awareness of orthopaedics as a possible career field may be improved through a mentoring program designed and delivered by orthopaedic residents.Methods. A five-resident QI team developed four educational sessions aimed at a medical student audience. Forum topics included (1) orthopaedics as a career, (2) fracture conference, (3) splinting workshop, and (4) residency application process. Pre- and post-forum surveys were administered to student participants to assess changes in their perceptions regarding orthopaedic surgery. Data derived from the questionnaires were analyzed with nonparametric statistical tests.Results. Of 18 forum participants, 14 were men and 4 were women. A total of 40 survey pairs were collected, averaging 10 per session. In the all-participant encounter analysis, there were statistically significant improvements in all outcome measures including interest in, exposure to, and knowledge of orthopaedics; exposure to our training program; and ability to interact with our residents. Those undecided regarding their specialty demonstrated larger increases in post-forum responses, suggesting that the learning experience was more impactful for that subgroup.Conclusions. This QI initiative was a successful demonstration of orthopaedic resident mentorship of medical students, wherein perceptions of orthopaedics were favorably influenced by the educational experience. For some students with limited access to orthopaedic clerkships or formal one-on-one mentoring, forums like these may be an acceptable alternative.